The Customer Satisfaction as an Antecedent of Purchase Decision in the Post Pandemic Era - Madiawati, Putu Nina; Pardede, Nova Lina Kristin (Universitas Mercu Buana, 2023)
Objectives: People's consumption habits have changed because of the pandemic which has been ongoing for about a year. The government's execution of the PSBB strategy has had a significant negative impact on local economic activity, particularly the food industry. Regional food and souvenirs are among the most potential industries that may grow following the COVID-19 pandemic. people visit one of these places since it has its own distinctive qualities and to remember, people bring home some souvenirs. The goal of this study is to determine whether consumer satisfaction can affect buying choices following the Covid-19 epidemic. Methodology: The study's quantitative approach makes use of purposive sampling of 100 participants and structural equation modeling (SEM) analysis methods with SmartPLS 3.0 software.Finding: The findings of the study indicate that product quality, brand image, and sales promotion significantly impact purchasing decisions. This suggests that these factors play a crucial role in shaping consumer choices. Additionally, the study reveals that purchasing decisions significantly influence consumer satisfaction. The level of consumer satisfaction with a product positively correlates with the likelihood of choosing to buy Tebing Tinggi's souvenir items. These findings highlight the importance of consumer happiness in influencing buying decisions, particularly in the post-Covid-19 epidemic environment. Conclusion: This study demonstrates that consumer satisfaction can indeed affect buying choices following the Covid-19 epidemic. The results emphasize the significance of product quality, brand image, and sales promotion in shaping purchasing decisions. Moreover, the study underscores the importance of consumer satisfaction as a determinant of buying behavior. These findings have implications for businesses operating in the post-pandemic environment, highlighting the need to prioritize factors that contribute to consumer happiness in order to drive sales and improve overall customer satisfaction.